Excimer-based activatable fluorescent sensor for sensitive detection of alkaline phosphatase - Yuan, Fang (2022)
The accurate detection of related biomarkers at early stage is crucial in diagnosis and therapy of cancer. Small molecule fluorescence probes stand out acting as efficient tools to detect biomolecules, especially biomacromolecules. Herein, a new probe that features excimer formation has been designed to detect cancer-related biomarker alkaline phosphatase(ALP). The probe shows high sensitivity to ALP with a low limit detection of 0.13 U/L and high selectivity with resistance to the interference in the complex physiological system. Furthermore, this probe presents good biocompatibility with negligible cytotoxicity and displays remarkable cell imaging functions, which allows for its application in biosystems. Theoretical simulation validates the high affinity of the probe with ALP and depicts the details of the interaction modes, which provides the possible mechanisms underlying the efficient detection of the probe in atomic level. The study of synthesis, properties and applications of the activatable emissive excimers not only enriches the tools to detect ALP, but also provides a new strategy to comprehend the pathogenic mechanism of enzyme-related diseases.